2010
DOI: 10.1542/peds.2009-2826
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Auditory Processing Disorder in Children

Abstract: Presenting symptoms of APD were largely unrelated to auditory sensory processing. Response variability and cognitive performance were the best predictors of poor communication and listening. We suggest that APD is primarily an attention problem and that clinical diagnosis and management, as well as further research, should be based on that premise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
304
2
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(348 citation statements)
references
References 33 publications
23
304
2
19
Order By: Relevance
“…Because IMAP minimizes procedural confounds, and children cannot begin the test until they demonstrate they understand it, we can be confident in ascribing the different performances of these two children to test-specific factors for each child. The inclusion in the IMAP battery of paired AP tests 5 and a range of cognitive tests further permits us to explore the reasons for this individual variation. We recently completed a UK population-based study using IMAP 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Because IMAP minimizes procedural confounds, and children cannot begin the test until they demonstrate they understand it, we can be confident in ascribing the different performances of these two children to test-specific factors for each child. The inclusion in the IMAP battery of paired AP tests 5 and a range of cognitive tests further permits us to explore the reasons for this individual variation. We recently completed a UK population-based study using IMAP 5 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that deficits seen in children with impaired auditory processing might not only arise from deficits in the ascending auditory pathway (bottom-up) but also from impaired top-down processes possibly also affecting the efferent central auditory system, i.e., structures that mediate auditory processing by attention and memory (Moore et al 2010;Moore 2012). Other studies reported that correlations between auditory tasks and cognitive measures are weak or non-existent (Rosen et al 2010), and that, in those children, attention and memory only explain a small amount of variance (Sharma et al 2009).…”
Section: Discrimination Deficits and Possible Top-down Engagementmentioning
confidence: 99%
“…There is no doubt that any test performed by a child uses cognitive resources. However, some researchers argue that APD is, at least partially, caused by higher-order impairments (Moore et al 2010;BSA 2011), while others claim that APD and attentional problems are not always interrelated (Sharma et al 2009). Second, there is an ongoing debate about the relation of APD and neurodevelopmental disorders such as specific language impairment (SLI) and dyslexia (King et al 2003;Sharma et al 2006Sharma et al , 2009Ferguson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several reviews and studies give an indication that APD tends to coexist with learning and language disorders [1] . There is evidence that shows that higher-order cortical functions, particularly attention, play a role in problems with listening, which implies that this is not a problem of the auditory pathway on its own [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, these patients tend to provide inappropriate responses when asked for particular information [4][5][6] . It has also been reported that children referred for testing for APD generally have other forms of deficiencies, mainly in cognitive function and attention [3] .…”
Section: Introductionmentioning
confidence: 99%